Final answer:
To solve the system of equations, substitute the value of y from equation (2) into equation (1) to get x. Then, substitute the value of x into equation (2) to get y. The solutions are x = -3 and y = 7.
Step-by-step explanation:
To solve the system of equations:
2x – 4y = -34 ---(1)
-3x - y = 2 ---(2)
First, let's solve equation (2) for y:
y = -3x - 2
Now substitute this value of y into equation (1):
2x - 4(-3x - 2) = -34
Simplify the equation:
2x + 12x + 8 = -34
Combine like terms:
14x + 8 = -34
Subtract 8 from both sides:
14x = -42
Divide both sides by 14:
x = -3
Now substitute the value of x into equation (2) to solve for y:
-3(-3) - y = 2
Simplify the equation:
9 - y = 2
Subtract 9 from both sides:
-y = -7
Divide both sides by -1:
y = 7
Therefore, the solutions to the system of equations are:
x = -3
y = 7